1984
DOI: 10.1080/00039896.1984.10545862
|View full text |Cite
|
Sign up to set email alerts
|

A Report of Occupational Deaths Attributed to Fluorocarbon-113

Abstract: This study reports two occupational deaths resulting from exposure to fluorocarbon-113 (1,1,2-trichloro-1,2,2-trifluoroethane; FC-113) in enclosed and confined spaces. One incident involved a worker who was exposed to FC-113 after entering a small degreasing tank to clean it. The second case involved a significant spill of FC-113 onboard a marine vessel. The incidents are compared to other fatal exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These studies link arrhythmias to "epinephrine sensitization," in which the myocardium's transmembrane electrical milieu is altered by the halocarbon to become more sensitive to catecholamineinduced arrhythmias. Although many fluorocarbons alone can cause arrhythmias at high exposure levels, some fluorocarbons produce serious arrhythmias in mammals at exposure levels as low as 5,000 ppm, when combined with intravenous epinephrine at tachycardia-producing doses [Reinhardt et al, 19711. There have been several cases of presumed cardiac sudden death with workplace exposure to these chemicals, especially to CFC 1 13 (1,1,2-trichloro-l,2,2-trifluoroethane), and 1 , l , l -trichloroethane [Hatfield and Maykoski, 1970;Jones and Winter, 1983;May and Blotzer, 1984;Lehmann, 1980;Yonemitsu et al, 1983;Clark et al, 1985;NIOSH, 19891. In addition, the widely used fire extinguishing agent, halon 121 1, has caused sudden death when abused for recreation and, most recently, when used to extinguish a fire in a confined space [Smeeton and Clark, 1985;Steadman et al, 1984;Lerman et al, 19911.…”
Section: Subjectmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies link arrhythmias to "epinephrine sensitization," in which the myocardium's transmembrane electrical milieu is altered by the halocarbon to become more sensitive to catecholamineinduced arrhythmias. Although many fluorocarbons alone can cause arrhythmias at high exposure levels, some fluorocarbons produce serious arrhythmias in mammals at exposure levels as low as 5,000 ppm, when combined with intravenous epinephrine at tachycardia-producing doses [Reinhardt et al, 19711. There have been several cases of presumed cardiac sudden death with workplace exposure to these chemicals, especially to CFC 1 13 (1,1,2-trichloro-l,2,2-trifluoroethane), and 1 , l , l -trichloroethane [Hatfield and Maykoski, 1970;Jones and Winter, 1983;May and Blotzer, 1984;Lehmann, 1980;Yonemitsu et al, 1983;Clark et al, 1985;NIOSH, 19891. In addition, the widely used fire extinguishing agent, halon 121 1, has caused sudden death when abused for recreation and, most recently, when used to extinguish a fire in a confined space [Smeeton and Clark, 1985;Steadman et al, 1984;Lerman et al, 19911.…”
Section: Subjectmentioning
confidence: 97%
“…Experimental studies in animals have demonstrated these effects at exposure concentrations above permissible exposure levels [Zakhari and Aviado, 19821. Human arrhythmias and sudden death have been documented in cases of occupational overexposure and volatile substance abuse [May and Blotzer, 1984;Ramsey et al, 1989;Lerman et a]., 19911. It is not known whether or not lower exposure levels regularly encountered in the workplace, in concert with exertion, may increase the frequency of arrhythmias and the risk of sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…No adverse effects were noted in a population of workers exposed to average levels of 700 ppm with peaks to 4780 ppm (Imbus and Adkins 1972;NIOSH 1980). However, deaths of two workers have been reported when individuals have been overexposed to CFC 113, especially in "confined spaces" (May and Blotzer 1984). In one case, the exposure level was estimated to be 128,000 ppm; in the other, it was estimated to have been in the range of 6000-37,000 ppm for 15 min.…”
Section: Acute Toxicitymentioning
confidence: 99%
“…Although sudden occupational deaths among Freon 113 workers have been reported (May et al, 1984;Clark et al, 1985;Yonemitsu et al, 1983;, the cause of death still remains to be solved. A common feature of these industrial cases was hypoxia caused by Freon 113 accumulation at work sites since the gravity of Freon 113 is 6.47 times higher than air (May et al, 1984). Thus, in some reports , the cause of sudden death was ascribed to asphyxia.…”
Section: Introductionmentioning
confidence: 95%